The multidimensional comprehension of Chagas disease. Contributions, approaches, challenges and opportunities from and beyond the Information, Education and Communication (IEC) field - Sanmartino, Mariana (2021)
Chagas is a complex, multidimensional phenomenon in which political, economic, environmental, biomedical, epidemiological, psychological, and sociocultural factors intersect. Nonetheless, the hegemonic conceptualisation has long envisioned Chagas as primarily a biomedical question, while ignoring or downplaying the other dimensions, and this limited view has reinforced the disease?s long neglect. Integrating the multiple dimensions of the problem into a coherent approach adapted to field realities and needs represents an immense challenge, but the payoff is more effective and sustainable experiences, with higher social awareness, increased case detection and follow-up, improved adherence to care, and integrated participation of various actors from multiple action levels. Information, Education, and Communication (IEC) initiatives have great potential for impact in the implementation of multidimensional programs of prevention and control successfully customised to the diverse and complex contexts where Chagas disease persists.